Sugar-sweetened and artificially sweetened beverage consumption and risk of type 2 diabetes in men(1)(2)(3) - de Koning, Lawrence (American Society for Nutrition, 2011)
Background: Sugar-sweetened beverages are risk factors for type 2 diabetes; however, the role of artificially sweetened beverages is unclear. Objective: The objective was to examine the associations of sugar- and artificially sweetened beverages with incident type 2 diabetes. Design: An analysis of healthy men (n = 40,389) from the Health Professionals Follow-Up Study, a prospective cohort study, was performed. Cumulatively averaged intakes of sugar-sweetened (sodas, fruit punches, lemonades, fruit drinks) and artificially sweetened (diet sodas, diet drinks) beverages from food-frequency questionnaires were tested for associations with type 2 diabetes by using Cox regression. Results: There were 2680 cases over 20 y of follow-up. After age adjustment, the hazard ratio (HR) for the comparison of the top with the bottom quartile of sugar-sweetened beverage intake was 1.25 (95% CI: 1.11, 1.39; P for trend < 0.01). After adjustment for confounders, including multivitamins, family history, high triglycerides at baseline, high blood pressure, diuretics, pre-enrollment weight change, dieting, total energy, and body mass index, the HR was 1.24 (95% CI: 1.09, 1.40; P for trend < 0.01). Intake of artificially sweetened beverages was significantly associated with type 2 diabetes in the age-adjusted analysis (HR: 1.91; 95% CI: 1.72, 2.11; P for trend < 0.01) but not in the multivariate-adjusted analysis (HR: 1.09; 95% CI: 0.98, 1.21; P for trend = 0.13). The replacement of one serving of sugar-sweetened beverage with 1 cup (≈237 mL) of coffee was associated with a risk reduction of 17%. Conclusion: Sugar-sweetened beverage consumption is associated with a significantly elevated risk of type 2 diabetes, whereas the association between artificially sweetened beverages and type 2 diabetes was largely explained by health status, pre-enrollment weight change, dieting, and body mass index.